1999
DOI: 10.1136/jnnp.67.3.364
|View full text |Cite
|
Sign up to set email alerts
|

Different clinical aspects of debrancher deficiency myopathy

Abstract: Objective-To characterise the main clinical phenotypes of debrancher deficiency myopathy and to increase awareness for this probably underdiagnosed disorder. Methods-The diagnosis of debrancher deficiency was established by laboratory tests, EMG, and muscle and liver biopsy. Results-Four patients with debrancher deficiency myopathy were identified in the Tyrol, a federal state of Austria with half a million inhabitants. Clinical appearance was highly variable. The following phenotypes were diVerentiated: (1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Similar to previous studies, no correlation was found between muscle involvement and CK levels (17,18). It is thought that CK levels should be measured again in the follow-up.…”
Section: Discussionsupporting
confidence: 68%
“…Similar to previous studies, no correlation was found between muscle involvement and CK levels (17,18). It is thought that CK levels should be measured again in the follow-up.…”
Section: Discussionsupporting
confidence: 68%
“…Despite the fact that muscle glycogen is crucial for normal muscle energy metabolism, dynamic symptoms of exercise intolerance are not recognized in GSD III. 49 Unlike GSD V and VII, and distal glycolytic defects, exertional muscle contractures or recurrent rhabdomyolysis are not features of this disorder. 49,58 The fact that similar symptoms have not been described in GSD IIIa suggests that glycogen branches accessible to myophosphorylase (enzyme deficient in GSD V) provide sufficient anaerobic glycogenolysis to be protective.…”
Section: Implications For Muscle Energy Metabolism and Exercisementioning
confidence: 97%
“…48 Although rarely performed in the clinical scenario of GSD III, forearm exercise testing will demonstrate a blunted increase in lactate in GSD III. 49 Uric acid levels could also be elevated in the setting of muscle exertion. 50 Hepatomegaly and/or myopathy often lead gastroenterologists and neurologists to biopsy the liver or muscle/nerve to differentiate among the diverse causative factors in the differential diagnosis.…”
Section: Clinical and Laboratory Evaluationmentioning
confidence: 99%
See 2 more Smart Citations